Impact of Gujjar Rehabilitation Programme on the group size of Asian elephants (Elephas maximus) in Rajaji National Park, North-West India - RITESH JOSHI (Society for Indonesian Biodiversity, 2015)
Abstract. Joshi R. 2015. Impact of Gujjar Rehabilitation Programme on the group size of Asian elephants (Elephas maximus) in Rajaji National Park, North-West India. Biodiversitas 16: 188-195. A comparative study has been done to assess the impact of the Gujjar Rehabilitation Programme on the group’s size of Asian elephants (Elephas maximus) in Rajaji National Park, north-west India. Field surveys were carried out before the Gujjar’s rehabilitation during 1999-2001 and after the Gujjar’s rehabilitation during 2006-2008 in Chilla and Haridwar forest ranges of the park. A total of 833 groups of elephants were sighted, varying from 2-5 (mean value ±SD =28.5 ± 24.7) to 21-25 animals (mean value±SD=8.2±4.6). The number of groups sighted in Haridwar forest after the Gujjars’ rehabilitation were significantly low in summer and winter as compared before the Gujjars’ rehabilitation. However, the number of groups sighted in Chilla forest before and after the Gujjars’ rehabilitation in both the seasons was found to be same. Results indicated that elephant’s group’s size and movement was shrinking/reducing in Haridwar forest, however, in Chilla forest it was found to be slightly expanding/ increasing. The impact of Gujjar Rehabilitation Programme has not brought any drastic change in restoring the larger population of elephants and in increasing their group’s size, however, this has increased the frequent movement and activities of elephants within their home range. Restoration of large fragmented forest stretches/corridors for elephant’s migration and habitat management are of paramount importance in providing elephants a wider way to move across entire landscape in large herds. As increase in human population in the nearby areas and developmental activities, with increase in vehicle traffic pressure on national highways and railway track existing across the park were found to be creating negative impacts on the overall movement of large groups of the elephants.